Back to the Future: Implications for the Field of HRM of the Multistakeholder Perspective Proposed 30 Years Ago - Beer, Michael; Boselie, Paul; Brewster, Chris (Human Resource Management, 2015)
Thirty years on from the seminal works on human resource management (HRM) by Beer et al., we examine how the subject has developed. We offer a normative review, based on that model and critique the assumption that the business of HRM is solely to improve returns to owners and shareholders. We identify the importance of a wider view of stakeholders to practitioners and how academic studies on the periphery of HRM are beginning to adopt such a view. We argue that the HRM studies so far have given us much valuable learning but that the subject has now reached a point where we need to take a wider, more contextual, more multilayered approach founded on the long‐term needs of all relevant stakeholders. The original Beer et al. model remains a valuable guide to the next 30 years of HRM. © 2015 Wiley Periodicals, Inc.